2005
DOI: 10.1080/03067310500142325
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria and microcystins occurrence in the Guadiana River (SW Spain)

Abstract: This work reports on the survey carried out to determine the presence of microcystins (MCs) by using ELISA tests and HPLC-UV for such determination in different sample sites along the Spanish course of the Guadiana River. The most important cyanobacteria species identified were, Microcystis aeruginosa and Oscillatoria spp. The highest total microcystin content recorded was 6.40 mg L À1 in 2002. The main toxins found were microcystins RR and LR, with microcystin YR present at trace levels. Improvements in sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
4
10
1
2
Order By: Relevance
“…A similar situation was observed in summer 2003, for example, in the Guadiana River (SW Spain) (Moreno et al, 2005) where maximum cyanobacterial cell density reached about 16 million cells per ml. The presence of high phytoplankton biomass in surface waters, including rivers and streams, is commonly related to an excess of nutrients.…”
Section: Discussionsupporting
confidence: 62%
“…A similar situation was observed in summer 2003, for example, in the Guadiana River (SW Spain) (Moreno et al, 2005) where maximum cyanobacterial cell density reached about 16 million cells per ml. The presence of high phytoplankton biomass in surface waters, including rivers and streams, is commonly related to an excess of nutrients.…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, Meridion circulare, characteristic of low conductivity streams (Rott et al, 1998) was present (0.15% of total community) in 1 of 4 weeks, while Gomphoneis olivacea, characteristic of low orthophosphate (Rott et al, 1998) was present (0.009-0.09% of total community) in 2 of 4 weeks. Aphanizomenon flos-aquae is a blooming cyanobacteria that can create nuisance and low dissolved oxygen conditions in rivers (Kromer et al, 1981;Moreno et al, 2005) and the Great Lakes, although levels in Lake Erie declined considerably between 1970 and 1983-85 (Makarewicz and Bertram, 1991). A. flos-aquae was not observed in any of the samples from the Ohio St. Bridge.…”
Section: Phytoplankton Community Structurementioning
confidence: 64%
“…However, studies recently have reported the presence of microcystin toxins in the lower Great Lakes (Brittain et al, 2000;Murphy et al, 2003;Boyer, 2006;Makarewicz et al, 2006). Microcystin is a hepatotoxin that has been linked to animal mortalities, increased incidence of gastrointestinal infections, vomiting and diarrhea, and liver cancers (e.g., Ueno et al, 1996;Falconer, 2005;Moreno et al, 2005;Lehman 2007). Due to high levels of microcystin (up to 239 μg/L), a warning was issued and posted around Hamilton Harbor in 2001, describing the risks of contact and recommending that people not eat fish caught in the Harbor.…”
Section: Introductionmentioning
confidence: 99%
“…In the Bogialli's [37,38], which affected the extraction efficiency. Therefore, the specific solution to dissociate the covalent bound between MCs and PP-1or PP-2A [36], the use of immunoaffinity cartridges (IAC) [39], and the appropriate method for MCs analysis should be taken into consideration for better recovery in fish tissues. Although the new method was more sensitive than the colorimetric assay, problems associated with a low reproducibility at random were also observed during the recovery analyses in our experiment, which may be due to the sample-handling operations (extraction, dilution) or the characteristics of the sensitive chemiluminscent analytical method used in our experiment (or both).…”
Section: Accuracy Evaluation Of the Proposed Methodsmentioning
confidence: 99%